A Bivalent Role of Genistein in Sprouting Angiogenesis - Berndt, Sarah; Issa, Mark E.; Carpentier, Gilles; Cuendet, Muriel (Planta Medica, 2018)
The effects of genistein on angiogenesis remain poorly understood. Some studies claim an antiangiogenic effect and others claim a pro-angiogenic one. Thus, the aim of this study was to determine if genistein may exhibit bivalent angiogenic effects. To address this question, genistein angiogenic modulatory effects were examined using an in vitro 3D angiogenesis model using human umbilical vein endothelial cells. In this model, a bivalent effect of genistein was demonstrated on sprouting angiogenesis, with angiogenic stimulation at low concentrations (0.001 – 1 µM) and inhibition at higher ones (25 – 100 µM). Enhancement of the endothelial tube formation correlated with an increase in human umbilical vein endothelial cell metabolic activity and proliferation. Inhibition of angiogenesis correlated with a decreased metabolic activity, proliferation, and migration. Moreover, high concentrations of genistein influenced human umbilical vein endothelial cell morphology. Expression of genes involved in the angiogenic process in response to genistein was measured to study the mechanism of action. Secretome profiling revealed that angiogenic regulators were modulated with genistein treatment. These results suggested a bivalent effect of genistein on human umbilical vein endothelial cell growth and angiogenesis, and further investigations on the benefit of genistein for cancer chemoprevention, cancer treatment, or pro-angiogenic therapies have to be carefully considered.
Keywords: angiogenesis; genistein; HUVECs; sprouting